Pengaruh Brand Equity Dan Brand Engagement Terhadap Brand Loyalty. (Studi Kasus Pada Pelanggan Awesam Store Suhat, Malang) - Kurniawan, Alfian Bangkit; Mawardi, Muhammad Cholid; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of brand equity and brand engagement on brand loyalty among customers of Awesam Store Suhat, Malang. The research employed a quantitative approach with an explanatory research design. The sample was determined using purposive sampling, and data were collected through an online questionnaire. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that brand equity has a positive and significant effect on brand loyalty, while brand engagement exerts a significant negative influence. Collectively, both variables are proven to contribute significantly to the formation of customer loyalty. These findings suggest that strengthening brand equity is a more effective strategy for enhancing loyalty, whereas the current approach to brand engagement should be re-evaluated to achieve a more constructive impact. Keywords: Brand Equity, Brand Engagement, Brand Loyalty